A Course in phonetics - Ladefoged, Peter; Johnstone, Keith (Cengage Learning, 2015)
Suitable for the study of phonetics, this book introduces concepts of speech production, describes speech in acoustic terms, and teaches practical phonetic skills including IPA transcription.